A novel cyclopalladated complex with a diferrocenyl Schiff base ligand: Synthesis, structure, electrochemical and catalytic properties. (8th January 2015) - Han, Li-Min; Ke, Chun-Long; Zhang, Dan-Zhao; Gao, Yuan-Yuan; Zhu, Ning; Xie, Rui-Jun; Wang, Ya-Qi; Suo, Quan-Ling
Abstract : Graphical abstract: The N-(diferrocenylmethylene)aniline ligand Fc2 C = NPh (1 ) and a novel cyclopalladated complex (Fc2 C = NPh)PdClPPh3 (2 ) have been synthesized and characterized. Electrochemistry reveals a strong electronic communication between the two ferrocenyl units in2 . Complex2 is also an active catalyst for the Suzuki coupling reaction. Abstract: The N-(diferrocenylmethylene)aniline Schiff base Fc2 C = NPh (1 ) (Fc = ferrocenyl, Ph = phenyl) was synthesized by the reaction of diferrocenyl-methanone with aniline, and its structure was determined for the first time in this paper. The crystal structure of the novel cyclopalladated complex (Fc2 C = NPh)PdClPPh3 (2 ) was analyzed by single crystal X-ray diffraction. The structure of ligand1 displays an anti-configuration for the ferrocenyl groups bonded to the C atom of the CN bond lying on the opposite side to the phenyl ring. The structure of complex2 shows a four-coordinated structural type and the two ferrocenyl moieties bridged through the C atom of the CN bond remain in the anti-configuration; the structure also contains a bicyclic system of the coordinated Cp ring and a five-membered metallacycle. The electrochemical properties of ligand1 and complex2 were studied by cyclic voltammetry, and the results reveal that there is a stronger electronic communication between the two ferrocenyl units in2 . The results of a catalytic evaluation show that complex2 is highly active as a catalyst for the Suzuki CC coupling reaction and the biphenyl product gotten in this reaction can be obtained in 93% yield.